2010
DOI: 10.1080/13803391003683062
|View full text |Cite
|
Sign up to set email alerts
|

Capacity to make medical treatment decisions in multiple sclerosis: A potentially remediable deficit

Abstract: Ability to make decisions about medical treatment is compromised in significant numbers of people with neurological and psychiatric illness, and this incapacity frequently corresponds with compromised neuropsychological function. Although cognitive deficits occur often in people with multiple sclerosis (MS), no research has studied decisional capacity in that disease. The present investigation examined ability to understand treatment disclosures, which is a core component of decisional capacity, in 36 people w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Third, the risk factors for decisional incapacity associated with the psychiatric diagnoses listed above may be no greater than those associated with several medical conditions (Basso et al 2010; Luebbert et al 2008). …”
Section: Resultsmentioning
confidence: 99%
“…Third, the risk factors for decisional incapacity associated with the psychiatric diagnoses listed above may be no greater than those associated with several medical conditions (Basso et al 2010; Luebbert et al 2008). …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, as many as 65% of patients manifest significant cognitive impairment (Chiaravalloti & DeLuca, 2008; Rao, Leo, Bernardin, & Unverzagt, 1991a), and these deficits correspond with degraded activities of daily living (Basso, Shields, Lowery, Ghormley, Combs, Arnett, & Johnson, 2008; Chiaravalloti, DeLuca, Moore, & Ricker, 2005; Rao, Leo, Ellington, Nauertz, Bernardin, & Unverzagt, 1991b). For instance, neuropsychological dysfunction correlates with increased unemployment, diminished work performance, reduced psychosocial function, compromised ability to provide informed consent to medical treatment, and degraded management of daily domestic activities (Basso, Candilis, Johnson, Ghormley, Combs, & Ward, 2010; Baughman, Basso, Sinclair, Combs, & Roper, 2015; Rao et al, 1991b). …”
mentioning
confidence: 99%
“…Yet, studies with other populations have also found support for the relationship between EF and autonomy. For instance, much research examining decision-making capacity, a specific manifestation of autonomy, has found that higher EF predicts more independence in medical decision making (e.g., Basso et al, 2010; Dreer, DeVivo, Novack, Krzywanski, & Marson, 2008).…”
mentioning
confidence: 99%